Chapter 1 The role of trade credit in corporate activity - Koralun-Bereźnicka, Julia (Taylor & Francis, 2021)
This chapter describes the role of trade credit in the functioning of enterprises. It presents the essence and the use of this form of finance, as well as placing it in a historical context. The chapter discusses the role of trade credit and the methods of trade credit management in business entities. It also describes the rules of trade credit administration, as well as the common reasons that enterprises use trade credit. Moreover, the chapter discusses the receivables and payables management system in an enterprise. Apart from highlighting the role of trade credit in national economies, it indicates the tools for minimising the level of risk associated with the trade credit granted. Further on, it presents the various objectives that trade credit allows entrepreneurs to achieve. Finally, it reports the legislative regulations introduced to exclude deferred payment contracts, which can be grossly unfair to one of the parties.